Cefiderocol, a Siderophore Cephalosporin for Gram‐Negative Bacterial Infections: Pharmacokinetics and Safety in Subjects With Renal Impairment. (22nd November 2016) - Katsube, Takayuki; Echols, Roger; Arjona Ferreira, Juan Camilo; Krenz, Heidi K.; Berg, Jolene Kay; Galloway, Christopher
Abstract: Cefiderocol, a new injectable siderophore cephalosporin antibiotic, has promising in vitro and in vivo activity against Gram‐negative bacteria including multidrug‐resistant Pseudomonas aeruginosa, Acinetobacter baumannii, and Klebsiella pneumoniae . Cefiderocol is mainly renally eliminated. The pharmacokinetics and safety of cefiderocol in subjects with renal impairment were assessed following a single 1000‐mg intravenous 1‐hour infusion of cefiderocol. Subjects with mild, moderate, or severe renal impairment and end‐stage renal disease (ESRD) requiring hemodialysis were compared with demographically (age, body mass index, and sex) matched healthy subjects with normal renal function. The effect of hemodialysis on the clearance of cefiderocol was also assessed. Total drug clearance from plasma (CL) and terminal half‐life (t1/2 ) correlated with renal function. Ratios (90% confidence intervals) of area under the plasma concentration‐time curve from 0 to infinity (AUC) in mild, moderate, severe, and ESRD groups compared to those with normal renal function were 1.0 (0.8‐1.3), 1.5 (1.2‐1.9), 2.5 (2.0‐3.3), and 4.1 (3.3‐5.2), respectively. Maximum plasma concentration (Cmax ) was similar between renal‐impairment groups and the normal‐renal‐function group. Approximately 60% of cefiderocol was removed by hemodialysis for 3 to 4 hours. The plasma‐protein‐unbound fraction was similar between various renal function groups. The incidence of adverse events did not appear to have any correlation with the degree of renal impairment. Single 1000‐mg intravenous doses of cefiderocol were generally well tolerated in subjects with impaired renal function except for 1 subject who discontinued due to urticaria. In conclusion, renal impairment impacted AUC, CL, and t1/2 without affecting Cmax . Cefiderocol was significantly removed by intermittent hemodialysis.